IMPLEMENTASI PROGRAM BERAS UNTUK RUMAH TANGGA MISKIN (MISKIN) - Rudy Munandar E.21108069 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Problem The program of rice for poor households at Jeruju Besar village, sub district of  Kakap River, the regency of Kubu Raya is many people still do not totality understand about the program of rice for poor households especially    TH–AD (Target of Household-Advantage Giver). So in practice frequently happen misconception and mistakes interpretation. The research purpose to describe implementation distribution of the rice for poor household if view from organizing, interpretation and application. Method of this research is qualitative, data analysis was used qualitative data from the observation, interview, and documentation from the research object. The research result Implementation in the program of rice for poor households at Jeruju Besar village, sub district of  Kakap River is represent less of control and less transparency, so information access to the rice stakeholder  for the poor household especially TH – AD is not on target or less achievement the target of 6R that is right on the beneficiaries target , right on quantity, right on price, right on time, right on administration, and right on quality. The conclusion of research Implementation of  the program of rice for poor households at Jeruju Besar village, sub district of Kakap River is not appropriate with people expectation because of coordination team is not optimal to socialize the program of rice for poor households. Key Words: Implementation, Rice for Poor Household